Senyawa Fucoidan Pada Teripang Laut Untuk Pengobatan Diabetes Mellitus: Sebuah Tinjauan Pustaka - Wina Arsylia Fakar (Yayasan Pendidikan Medika Indonesia, 2023)
Diabetes Mellitus (DM) is a chronic disease characterized by blood glucose (blood sugar) levels exceeding normal, namely blood sugar levels at or above 200 mg/dl, and fasting blood sugar levels above or equal to 126 mg/dl. In the last few decades, the content of sea cucumber secondary metabolites has been widely studied, such as inhibiting the growth of new blood vessels, preventing excessive blood clotting, having antibacterial, anti-inflammatory, anticancer properties, including antidiabetes One of the sea cucumber compounds is Fucoidan, which is an acidic polysaccharide consisting of fucose monosaccharides and its chemical structure differs depending on the type of sea cucumber. Fucoidan has been widely proven to have potential in the treatment of diabetes.